Four Years Maternal Missed Mortality Ratio and Mortality Index at A Tertiary Care Hospital in Azad Kashmir - Ambreen Ehsan; Maryam Zubair; Abida Islam; Amera Tariq; Umairah Yaqub; Nosheena Shabbir (Pakistan Armed Forces Medical Journal, 2024)
Objective: To calculate the Maternal Near Miss Mortality Ratio and Mortality Index at a tertiary care hospital in a developing country with limited healthcare resources.